Analisis pengendalian kualitas pada proses produksi plat baja di PT XYZ menggunakan metode seven tools dan kaizen - Setiadi, Danang Amin; Winursito, Yekti Condro (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Xyz Company has a high awareness of maintaining production quality to ensure operational sustainability. This study aims to optimize the production process by minimizing defects in the future. The research was conducted through field observations and literature review, using company data as samples. The methods applied include Seven tools and Kaizen to analyze and improve the production process. Findings show that defects such as Scale, Round Wave, Scab, Defect on Surface Plate, Ultrasonic Test, Crack, Camber, and Flatness have high values. The recommendations suggest implementing continuous improvement with a focus on five key factors through Kaizen to enhance operational efficiency and foster a more collaborative and adaptive work culture.